Relationship of Inflammatory Cytokines From M1-Type Microglia/Macrophages at the Injured Site and Lumbar Enlargement With Neuropathic Pain After Spinal Cord Injury in the CCL21 Knockout (plt) Mouse - Honjoh, Kazuya; Nakajima, Hideaki; Hirai, Takayuki; Watanabe, Shuji; Matsumine, Akihiko (Frontiers in Cellular Neuroscience, 2019)
Spinal cord injury (SCI) causes loss of normal sensation and often leads to debilitating neuropathic pain (NeP). Chronic NeP develops at or below the SCI lesion in as many as 80% of patients with SCI, and may be induced by modulators of neuronal excitability released from activated microglia and macrophages. In the inflammatory response after SCI, different microglia/macrophage populations that are classically activated (M1 phenotype) or alternatively activated (M2 phenotype) have become of great interest. Chemokines have also recently attracted attention in neuron-microglia communication. CCL21 is a chemokine that activates microglia in the central nervous system and is expressed only in neurons with an insult or mechanical injury. In this study using an SCI model in mutant (plt) mice with deficient CCL21 expression, we assessed post-SCI NeP and expression of microglia/macrophages and inflammatory cytokines at the injured site and lumbar enlargement. SCI-induced hypersensitivities to mechanical and thermal stimulation were relieved in plt mice compared with those in wild-type (C57BL/6) mice, although there was no difference in motor function. Immunohistochemistry and flow cytometry analysis showed that the phenotype of microglia/macrophages was M1 type-dominant in both types of mice at the lesion site and lumbar enlargement. A decrease of M1-type microglia/macrophages was seen in plt mice compared with wild-type, while the number of M2-type microglia/macrophages did not differ between these mice. In immunoblot analysis, expression of M1-induced cytokines (TNF-α, IFN-γ) was decreased in plt mice, while that of M2-induced cytokines (IL-4, IL-10) did not differ in the two types of mice. The results of this study indicate that suppression of expression of inflammatory cytokines by decreasing the number of M1-type microglia/macrophages at the injured site and lumbar enlargement is associated with provision of an environment for reduction of NeP. These findings may be useful for design of new therapies to alleviate NeP after SCI.